ASUPAN DAN KECUKUPAN GIZI ANTARA REMAJA OBESITAS DENGAN NON OBESITAS - Nadia Loliana; Siti Rahayu Nadhiroh (Media Gizi Indonesia, 2015)
Nutrition issues in adolescents arise because of inappropriate dietary habit, causing an imbalance between nutritional  intakes and the recommended dietary allowances. The prevalence of obesity in adolescents increased within the last 30 years. The percentage of adolescents aged 12-19 years who were obese increased from 18,4% in 2009-2010 to 20,5% in 2012. Obesity occurred because of behavior and habit of adolescent who consume high calorie food excessively. The aim of this research was to analyze the difference of intake and nutritional adequacy between obese and nonobeseadolescents. This study was an analytical observational research with cross sectional design. The sample was 46 Senior High School students that divided into 23 obese and 23 non obese adolescent groups chosen by simple random sampling. The obesity data was obtained from the results of anthropometric measurements, while intake and nutritional adequacy were obtained from 2x24 hours food recall form. Mann Whitney test was used to analyze the difference between variable. The research revealed that there was a difference of energy intake, carbohydrates, protein, and fat with p-value 0,01, 0,00, 0,038 and 0,018 respectively, and nutritional adequacy of energy, carbohydrates, protein, and fat with 0,02, 0,00, 0,017 and 0,018 respectively between obese and non-obese adolescents. It can be concluded that there is a difference of intake and nutritional adequacy between obese and non-obese adolescents. Providing information and education about obesity, it risks, and healthy diet are recommended to prevent obesity.Keywords: intake, nutritional adequacy, obesity, adolescents